Prisoners in the community: the open prison model in Catalonia - Marta Martí (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Open prisons are low-security penitentiary institutions in which life conditions are less strict than in closed prisons, and where prisoners have more contact with the outside world. Despite sharing important features, some variations can be found in the model of open prisons in different countries. This article describes the Catalan open prison model, characterized by the fact that prisoners serve the sentence in full semi-liberty; that is, by day they work and spend time with their families or doing other activities, but return to prison to sleep. As a contribution to the comparative study of open prisons, I describe here how Catalan open prisons are run and discuss the concept of ‘openness’ with reference, above all, to the open prisons that exist in Scandinavian countries. This work shows that the degree of openness of open prisons varies considerably between different countries – therefore approaching community penalties or closed prisons in a greater or lesser extent – and suggests that the role that open prisons are granted in each penal system is part of the explanation.1